1988
DOI: 10.1128/jvi.62.9.3265-3273.1988
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus type 12 E1B 19-kilodalton protein is not required for oncogenic transformation in rats

Abstract: The adenovirus type 12 mutants in700 and pm700 carry site-specific mutations within the reading frame encoding the E1B 19-kilodalton protein (19K protein) which prevent the production of the intact 19K protein. In cultures of human A549 cells, these mutants grow just as well as the wild-type virus does, but they display a large-plaque (Ip), cytocidal (cyt) phenotype. DNA in these infected cells is not degraded, but at late times in human KB cells infected by the mutants, the mutants display a DNA degradation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 60 publications
5
35
2
Order By: Relevance
“…Ad12 pm700 (E1B 19K-null) replicated to the same level as wt virus in all cell lines tested (Fig. 2, light-hatched bars, lanes 1 to 7), as previously demonstrated (18). Again, there were no constraints upon replicative capacity imposed by the host cell with respect to p53 status.…”
Section: Replication Of Wt Ad5 Is Independent Of Host Cell P53 Statussupporting
confidence: 82%
See 1 more Smart Citation
“…Ad12 pm700 (E1B 19K-null) replicated to the same level as wt virus in all cell lines tested (Fig. 2, light-hatched bars, lanes 1 to 7), as previously demonstrated (18). Again, there were no constraints upon replicative capacity imposed by the host cell with respect to p53 status.…”
Section: Replication Of Wt Ad5 Is Independent Of Host Cell P53 Statussupporting
confidence: 82%
“…Ad12 dl620, which contains a large in-frame deletion in the E1B 54K ORF from nucleotides 2129 to 2825, has been described previously (12,29). Ad12 hr703, a host range mutant restricted for growth in A549 cells and HeLa cells, contains a point mutation at amino acid 134 of E1B 54K, converting a Gln to a termination codon (12), and Ad12 pm700, an E1B 19K-null adenovirus that expresses E1A and E1B 54K, has also been described previously (18). Ad5 viruses were grown on permissive Ad5 E1 HEK 293 cells, while Ad12 viruses were grown on permissive Ad12 E1-transformed HER3 cells, to produce hightiter stocks.…”
Section: Methodsmentioning
confidence: 99%
“…A549 cells derive from a human small cell lung carcinoma and were used for some viral infection experiments. A549 cells were infected with wt Ad5 and Ad12 and with the E1B 19K Ϫ viruses Ad2 pm1722 (Barker and Berk, 1987) and Ad12 pm700 (Edbauer et al, 1988). Ad2 pm1722 is in a dl309 background, lacking part of the E3 gene.…”
Section: Cell Lines and Virus Infectionmentioning
confidence: 99%
“…A few years ago, we also came to a different conclusion about the role of the 19K product in oncogenic transformation induced by Adl2. We showed that 19K protein-deficient mutants of this oncogenic serotype were not defective for transformation of BRK and baby mouse kidney (BMK) primary cells in vitro or for direct induction of tumors by the virus in rats, although they failed to transform cells of the 3Y1 rat line (10). Stimulated by these results with Adl2, we have reexamined in detail the conditions for virus-induced transformation of rat and mouse cells by Ad5 and 19K mutants of this serotype.…”
mentioning
confidence: 96%
“…In some human cell types, 19K mutants display a DNA degradation (deg) phenotype, resulting in considerable breakdown of cellular and viral DNAs (3,32,43,52,63). Some of these mutants also show increased cytotoxicity (cyt phenotype) and form large plaques (Ip phenotype) in certain cell types (3,10,45,53,67).…”
mentioning
confidence: 99%